2003
DOI: 10.1080/1024533021000059474
|View full text |Cite
|
Sign up to set email alerts
|

Auto-immune Haemolytic Anaemia--a High-risk Disorder for Thromboembolism?

Abstract: An audit of the effect of anticoagulant prophylaxis in acute exacerbations of severe autoimmune haemolysis was undertaken. All cases of this disorder presenting to one institution over a 16 year period were reviewed. There were 28 patients who had a total of thirty six exacerbations of haemolysis. Anticoagulant prophylaxis had been introduced from 1992 following three cases with fatal pulmonary emboli. Venous thromboembolism occurred in 5 of 15 exacerbations without prophylaxis but in only one of 21 in which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 10 publications
2
54
0
4
Order By: Relevance
“…In all cases, the thrombotic manifestation occurred with active wAIHA, either at disease onset or during relapse. The link between AIHA and venous thrombosis has been reported since 1950 and the first series of AIHA and also in the setting of other inherited [20,21] but also acquired causes of hemolytic anemia such a paroxysmal nocturnal hemoglobinuria [22]. Patients with active wAIHA with a lupus anticoagulant [23], or those undergoing splenectomy [24] should be considered at high risk of thrombosis as 3 of 9 patients who underwent laparoscopic splenectomy experienced postoperative thrombosis of the portal vein system.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases, the thrombotic manifestation occurred with active wAIHA, either at disease onset or during relapse. The link between AIHA and venous thrombosis has been reported since 1950 and the first series of AIHA and also in the setting of other inherited [20,21] but also acquired causes of hemolytic anemia such a paroxysmal nocturnal hemoglobinuria [22]. Patients with active wAIHA with a lupus anticoagulant [23], or those undergoing splenectomy [24] should be considered at high risk of thrombosis as 3 of 9 patients who underwent laparoscopic splenectomy experienced postoperative thrombosis of the portal vein system.…”
Section: Discussionmentioning
confidence: 99%
“…1 In addition to increased thrombin and fibrin generation, increased tissue factor activity, and increased platelet activation (Figure 1), patients with hemolytic anemias manifest thrombotic complications, including venous thromboembolism, in situ pulmonary thrombosis and stroke. [1][2][3][4][5][6][7] Furthermore, the risk of thromboembolic complications appears to be higher following splenectomy. 1,3,6 The mechanism of coagulation activation in hemolytic anemias is likely multifactorial.…”
mentioning
confidence: 99%
“…If flares are unable to be prevented, general anticoagulation may be considered. In a small audit study of 28 patients, Hendricks found that anticoagulation in the form of unfractionated heparin, tinzaparin, and coumadin led to fewer instances of thromboembolism when given to hospitalized patients until their haemolysis stabilized [26]. Aside from haemolysis, other thrombosis risk factors to consider include history of prior DVTs, immobility, and recent surgery or trauma, as shown in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have been smaller in size or descriptive [5,26,27], done in the context of specific hyper coagulable states [28,29], or with a design that excluded secondary AIHA patients or lacked anon-AIHA cohort matched for relevant AIHA risk factors [14][15][16][17]19,20].…”
Section: Discussionmentioning
confidence: 99%